Is studying medicine good for your health? Long-term health outcomes of a cohort of clinical medicine graduates in England and Wales in the ONS Longitudinal Study. Issue 3 (18th March 2021) - Shelton, Nicola; Duke-Williams, Oliver; van der Erve, Laura; Britton, Jack; Xun, Wei
Abstract : Objective: To quantify the potential protective effect on health associated with study of a clinical medicine degree. Design: Prospective population-based cohort data collected at census and linked over time: cohort born before 1976 and survived to 2011. Subgroup analysis on those who reported having a degree at 1991 census. Setting: England and Wales population-based, including institutions. Participants: 159 116 men and 174 062 women; 13 390 men with degrees and 8143 women with degrees. Main outcome measure: Self-reported general health in 2011 based on logistic regression analysis. Results: Male graduates had 92% higher odds of having good or very good health than male non-graduates after adjustment for age and socioeconomic position (CI 1.82 to 2.03). Female graduates had 85% higher odds of having good or very good health than female non-graduates after adjustment for age and socioeconomic position (CI 1.73 to 1.98). Male clinical medicine graduates had 45% higher odds of having good or very good health than male humanities graduates after adjustment for age and socioeconomic position (CI 1.09 to 1.92). Male physical sciences graduates also had higher odds of having good or very good health than male humanities graduates after adjustment for age and socioeconomic position, but life sciences and social science graduates did not. There were no significant differences by degree subject for women. Conclusions: Male graduates in clinical medicine have higher odds of good self-reported health. Knowledge of medicine may confer a health advantage for men above that of other degrees.